2023
DOI: 10.1038/s41467-023-36338-x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering β-ketoamine covalent organic frameworks for photocatalytic overall water splitting

Abstract: Covalent organic frameworks (COFs) are an emerging type of crystalline and porous photocatalysts for hydrogen evolution, however, the overall water splitting activity of COFs is rarely known. In this work, we firstly realized overall water splitting activity of β-ketoamine COFs by systematically engineering N-sites, architecture, and morphology. By in situ incorporating sub-nanometer platinum (Pt) nanoparticles co-catalyst into the pores of COFs nanosheets, both Pt@TpBpy-NS and Pt@TpBpy-2-NS show visible-light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 52 publications
3
56
0
Order By: Relevance
“…The Brunauer–Emmett–Teller (BET) surface areas were calculated to be 497.9 m 2 g –1 for CityU-1 and 190.7 m 2 g –1 for CityU-2 (Figure a). The good crystallinity, permanent porosity, good stability, and uniform one-dimensional channel endow COFs to be excellent platforms in many applications. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The Brunauer–Emmett–Teller (BET) surface areas were calculated to be 497.9 m 2 g –1 for CityU-1 and 190.7 m 2 g –1 for CityU-2 (Figure a). The good crystallinity, permanent porosity, good stability, and uniform one-dimensional channel endow COFs to be excellent platforms in many applications. ,, …”
Section: Resultsmentioning
confidence: 99%
“…16 Currently, organic photocatalysts for the OWS without sacrificial donors are attractive but difficult to design. 17,18 One approach being the deposition of HER and OER co-catalysts, where the distribution of the two co-catalysts is critical. Another approach is to construct a Z schemes, whose complex device design and higher cost make it less attractive than a singlestep system, and where charge transfer requires overcoming additional processes related to the interface between the two materials.…”
Section: Requirement Of Sacrificial Donorsmentioning
confidence: 99%
“…Interestingly, systematically increasing the linker lengths in 2D COFs have been shown to decrease the band gaps. , This has been ascribed to the systematic variations in the valence band maximum (VBM) that are primarily delocalized on the linkers, while the conduction band minimum (CBM) is preferentially localized at the nodes, which are not affected by the linker length variations . Furthermore, the distribution of charge densities and their spatial separation in COFs have also been shown to be critically important for their photocatalytic applications. In this regard, Jin et al have shown that various combinations of nodes and linkers in sp 2 -carbon COFs can be used to tune the level of VBM and CBM, respectively, thus providing synthetic means to independently modulate the VBM and CBM through manipulating the structures of the nodes and linkers. Likewise, through an end-capping strategy, Yang et al synthesized vinylene-linked COFs end-capped with hydroxyl groups that showed modular band gaps and improved photocatalytic hydrogen evolution activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the distribution of charge densities and their spatial separation in COFs have also been shown to be critically important for their photocatalytic applications. In this regard, Jin et al have shown that various combinations of nodes and linkers in sp 2 -carbon COFs can be used to tune the level of VBM and CBM, respectively, thus providing synthetic means to independently modulate the VBM and CBM through manipulating the structures of the nodes and linkers. Likewise, through an end-capping strategy, Yang et al synthesized vinylene-linked COFs end-capped with hydroxyl groups that showed modular band gaps and improved photocatalytic hydrogen evolution activity. For a thorough review of the optoelectronic properties of COFs, the readers are referred to a recent review conducted by Keller and Bein …”
Section: Introductionmentioning
confidence: 99%